Kajian Kontemporer atas Dinamika Madrasah di Dunia Islam - Setyadi Sulaiman (Studia Islamika, 2008)
Book Review: Faris A. Noor, Yoginder Sikand, & Martin van Bruinessen (eds.), The Madrasa in Asia, Political Activism and Transnational Linkages, (ISIM, Amsterdam University Press, Amsterdam, 2008)As modern Islamic educational institutions, madrasahs do more than educate a new generation of ulama. They also function as effective venues for the dissemination of Islamic teachings. Developed later than pesantren, which, of course, are still full of shortcomings, madrasahswere developed in such a way that they were expected to help to create high civilization accompanying the strong progress of time The book under discussion is a collection of articles written by authors with a scholarly background and intends to address these questions and to study the most recent madrasah developments in the contemporary Muslim worldDOI: 10.15408/sdi.v15i3.528